2020
DOI: 10.3233/jpd-191786
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of LRRK2 Serine 935 Phosphorylation in Human Peripheral Blood Mononuclear Cells in Idiopathic Parkinson’s Disease and G2019S LRRK2 Cohorts

Abstract: The phosphorylated form of LRRK2, pS935 LRRK2, has been proposed as a target modulation biomarker for LRRK2 inhibitors. The primary aim of the study was to characterize and qualify this biomarker for therapeutic trials of LRRK2 inhibitors in Parkinson's disease (PD). To this end, analytically validated assays were used to monitor levels of pS935 LRRK2 and total LRRK2 in peripheral blood mononuclear cells (PBMCs) from the following donor groups: healthy controls, idiopathic PD, and G2019S carriers with and with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 26 publications
5
41
0
Order By: Relevance
“…Thus far, three assays have been published (Delbroek et al, 2013;Henderson et al, 2015;Scott et al, 2017), each utilizing a sandwich-ELISA approach by capture with a total LRRK2 antibody, followed by detection with a specific pS935-LRRK2 antibody. The latter two studies have facilitated accurate IC 50 measurements for LRRK2 kinase inhibitors from treated mouse tissues (brain and kidney) (Henderson et al, 2015), LRRK2 G2019S SH-SY5Y cell lysates (Scott et al, 2017), and human PBMC lysates (Padmanabhan et al, 2020). Notably, Meso Scale Discovery (MSD) has made a pS935-LRRK2 sandwich-ELISA-based assay commercially available, alongside a comparable assay that measures total LRRK2 protein levels.…”
Section: Elisa To Measure Lrrk2 Functionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus far, three assays have been published (Delbroek et al, 2013;Henderson et al, 2015;Scott et al, 2017), each utilizing a sandwich-ELISA approach by capture with a total LRRK2 antibody, followed by detection with a specific pS935-LRRK2 antibody. The latter two studies have facilitated accurate IC 50 measurements for LRRK2 kinase inhibitors from treated mouse tissues (brain and kidney) (Henderson et al, 2015), LRRK2 G2019S SH-SY5Y cell lysates (Scott et al, 2017), and human PBMC lysates (Padmanabhan et al, 2020). Notably, Meso Scale Discovery (MSD) has made a pS935-LRRK2 sandwich-ELISA-based assay commercially available, alongside a comparable assay that measures total LRRK2 protein levels.…”
Section: Elisa To Measure Lrrk2 Functionmentioning
confidence: 99%
“…In addition, the SIMOA assay is able to use sample volumes often <5 µL and run up to 400 samples per shift. A recent MJFF-led study (Padmanabhan et al, 2020) utilizing the SIMOA platform, reported levels as low as 19 pg/mL for total LRRK2 and 4.2 pg/mL for pS935-LRRK2 using full-length recombinant human LRRK2; and subsequently applied this approach to human PBMC lysates. Altogether, ELISA-based assays offer a more sensitive, high-throughput alternative to Western blotting with multiplex potential for measurement of pS935-LRRK2 biomarker levels.…”
Section: Elisa To Measure Lrrk2 Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, MJFF provided the group standardized clinical samples to enable head-to-head comparison of various high-throughput detection platforms. These efforts identified changes in LRRK2 activation in G2019S subjects by employing a highly sensitive pS935 LRRK2 assay [23] and demonstrated the potential to observe genotype-dependent shifts in LRRK2 inhibitor potency (based on pS935) in human peripheral blood mononuclear cells (PBMCs) that are likely chemotype specific (www.michaeljfox.org/mjff-scientific-publications-clinician-articles). The Consortium is now discussing methods to detect LRRK2 and its activation in the cerebrospinal fluid (CSF) and in immune cells such as monocytes and neutrophils given the high expression of LRRK2 in these cells [24].…”
Section: Establish and Improve Measures Of The Lrrk2 Pathwaymentioning
confidence: 99%